The Interconnection Between Arbitration and Commercial Courts: Scenarios, Issues, and A Proposal - Anangga W. Roosdiono; Muhamad Dzadit Taqwa; Mayta Ciara Salsabila (Journal of Private and Commercial Law, 2025)
There is a possibility that parties who have put an arbitration clause in their agreement may still bring bankruptcy or suspension of debt payment obligations before the Commercial Court (“Pengadilan Niaga”). In another scenario (Scenario 2), this situation can also—and often does—occur due to a third party, not bound by the arbitration clause, filing a bankruptcy petition against one of the parties. This article examines two key aspects when both forums are utilized: (1) the interrelation between these two forums in the context of the consequences of their respective decisions on each other; and (2) the conflicting principles, such as confidentiality and trust in arbitration versus public openness and distrust in Pengadilan Niaga. When one party ultimately submits a bankruptcy case to Pengadilan Niaga, the confidentiality of the dispute is compromised, and mutual trust is eroded. However, this reality is not strong enough to justify eliminating the potential overlap between arbitration and Pengadilan Niaga, given that scenarios where a third party files a bankruptcy petition can also occur. In such a scenario, the issue extends beyond the mere clash of principles. A proper framework to regulate the intersection between arbitration and Pengadilan Niaga needs to be formulated, taking into account the two scenarios that may arise.